Pelatihan Pemanfaatan Limbah Ikan Menjadi Pupuk Organik Cair (POC) di Kampung Terapung Danau Tempe, Kabupaten Wajo - Fitry Purnamasari; Sri Hardianti Rosadi; Ayu Saputri Bahar; Wardimansyah Ridwan (Yayasan Literasi Sains Indonesia, 2023)
The floating village of Lake Tempe is one of the villages around Lake Tempe, Wajo Regency. The livelihood of the community is generally fishing. Training on the use of fish waste into organic liquid fertilizer (POC) was carried out using lecture and demonstration methods. The Lecture Method is used to increase public understanding regarding the use of fish waste which can be used as Liquid Organic Fertilizer (POC) which is good for maintaining soil fertility and is beneficial for plants and helps reduce environmental pollution caused by fish waste. Next, a direct practice/demonstration was carried out regarding the methods for making the POC. Liquid organic fertilizer (POC), which uses fish waste, takes 14 days to make. The results of making liquid organic fertilizer (POC) were given to participants, not just giving it away but providing information on how to make fertilizer and the dosage for applying it so that residents and farmers could try and gain knowledge of making liquid organic fertilizer (POC). In this training activity, participants were very enthusiastic about taking part in the training, as evidenced by their enthusiastic attitude towards the material presented. The enthusiastic attitude of the training participants was shown through the many questions during the training. It is hoped that after this training activity is completed, participants will be interested in trying to apply it in their respective living environments.